Cloud Security in 21st Century: Current Key Issues in Service Models on Cloud Computing and how to overcome them - Sharma, Supern (2011)
Cloud computing is a disruptive innovation which offers new ways to increase capacity and capabilities of the organization’s IT infrastructure. In last few years cloud computing has taken computing industry by storm and many organizations are using cloud computing services to increase the efficiency, decrease their IT budgets and play an important role in defining the IT strategy of their business. Cloud computing offers various benefits such as scalability, elasticity, reducing IT expenditure considerably. Moreover, the architecture of such a utility computing consists of service models and deployment models which have been explained in the paper .Security is a key concern in all the web applications when they start interacting with applications in the public domain. The purpose of this paper is to provide the key security issues in service models of Cloud computing: Infrastructure-as-a-Service, Software-as-a-service and Platform-as-as-service. Finally, the paper will discuss some of the solutions been offered by cloud service providers for the following service models: Software as a service (SaaS), Platform as a service (PaaS) and Infrastructure as a Service (IaaS).